Maldives : 2005 Article IV Consultation-Public Information Notice; Staff Report; and Statement by the Executive Director for Maldives. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2005 Article IV Consultation with Maldives highlights that the Maldives suffered devastating damage from the December 2004 tsunami. Although human casualties were limited, damage to infrastructure has been extensive, with the cost of reconstruction estimated at nearly a half of gross domestic product. Reconstruction work has progressed slowly in 2005 but the pace is picking up. Recovery work has been slow due to insufficient coordination, problems in local consultation, and limited management capacity. The government and donors have been addressing these problems and the pace of implementation is finally accelerating. The 2006 budget is highly expansionary and threatens sustainability. The government has added to the fiscal deficit through new recruits, expansion of untargeted social programs, and a large domestically funded public investment program while using optimistic revenue projection. Fiscal reforms are of high priority. The report also explains that monetary policy should be geared to sustaining the peg arrangement based on indirect management. The objective of monetary policy should be to support the peg arrangement, which has served well as a credible nominal anchor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet